2022
DOI: 10.7150/ijbs.68216
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SQLE Contributes to Poor Survival in Head and Neck Squamous Cell Carcinoma

Abstract: Recently, increasing attention has been paid to the role of Squalene epoxidase (SQLE) in several types of cancers. However, its functional role in tumor progression of head and neck squamous cell carcinoma (HNSCC) is still unclear. We performed bioinformatic analyses and relative experiments to assess the potential mechanism of SQLE-mediated HNSCC malignancy. And the results showed that SQLE was significantly upregulated in tumor samples compared with peritumor samples. Mechanistically, miR-584-5p downregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Recent evidence has indicated that terbinafine may also exhibit potential anticancer properties. [ 34 ] Subsequently, we examined the efficacy of pharmacologically targeting SQLE on cisplatin response in an orthotopic mouse model and a PDX mouse model. The study design schematic is illustrated in Figure 8k .…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has indicated that terbinafine may also exhibit potential anticancer properties. [ 34 ] Subsequently, we examined the efficacy of pharmacologically targeting SQLE on cisplatin response in an orthotopic mouse model and a PDX mouse model. The study design schematic is illustrated in Figure 8k .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, HMGCR inhibitor simvastatin could also robustly enhances cancer vaccinations and synergizes with anti-PD-1 antibodies, which shows the broad therapeutic perspectives of drugs targeting cholesterol pathways in combination with other anti-tumor treatments ( 63 ). Apart from HMGCR, squalene monooxygenase (SM, also known as squalene epoxidase) which converts squalene to 2,3(S)-oxidosqualene is deemed as the second rate-limiting enzyme in cholesterol biosynthesis and its increased expression was also found associated with poor prognosis in several tumors like prostate cancer, pancreatic adenocarcinoma (PAAD) and head and neck squamous cell carcinoma (HNSCC) ( 64 66 ). While inhibition of SM could lead to the accumulation of squalene which further suppresses SCLC proliferation ( 67 ), and its pharmacological blockage also inhibits the invasion of CRPC ( 68 ).…”
Section: Lipid Metabolism Reprogramming In Tumor Cells and Tumor Stro...mentioning
confidence: 99%
“…Squalene epoxidase (SQLE) has been found to be highly expressed in HNSCC, and the SQLE-specific inhibitor Terbinafine shows promise as a candidate drug for clinical treatment. 49 In HNSCC, common variants of DNA repair mutations caused by HPV infection increase the efficacy of poly (ADP-ribose) polymerase (PARP) inhibitors. PARP inhibitors exhibit sensitization or synergistic effects with radiotherapy and platinum-based chemotherapy.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
“…Novel anti‐CTLA‐4 drugs, Tremelimumab and Ipilimumab, have been developed to counteract these co‐inhibitory receptors. Squalene epoxidase (SQLE) has been found to be highly expressed in HNSCC, and the SQLE‐specific inhibitor Terbinafine shows promise as a candidate drug for clinical treatment 49 …”
Section: Hpv‐associated Cancersmentioning
confidence: 99%